2022
DOI: 10.1021/acsestwater.2c00267
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer-Assembled Loose Nanofiltration Membrane for Persulfate Activity Enhancement: Performance and Process Regulation

Abstract: In this study, a Prussian blue analogue (PBA)-intercalated magnesium aluminum hydrotalcite (PBA–LDH) material was used to successfully modify the membrane surface by layer-by-layer synthesis with an intermediate layer inspired by dopamine polymerization (polydopamine (PDA)). The PBA–LDH@PDA membrane was endowed with highly efficient peroxymonosulfate (PMS) activation and superb antifouling properties. Quenching experiments implied that SO4 •– mainly contributed to the sulfadiazine (SDZ) degradation in the PBA–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Moreover, it has been reported that AM-PEI/HPAN LNF membranes showed resistance to membrane fouling with a flux recovery rate of over 98% [ 15 ]. While there have been numerous studies on LNF membranes, further evaluation and research are still needed to enhance their water flux performance, antifouling capabilities, and photocatalytic properties [ 16 , 17 ]. Continued research efforts can lead to the development of more efficient and versatile LNF membranes with enhanced performance in these critical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that AM-PEI/HPAN LNF membranes showed resistance to membrane fouling with a flux recovery rate of over 98% [ 15 ]. While there have been numerous studies on LNF membranes, further evaluation and research are still needed to enhance their water flux performance, antifouling capabilities, and photocatalytic properties [ 16 , 17 ]. Continued research efforts can lead to the development of more efficient and versatile LNF membranes with enhanced performance in these critical aspects.…”
Section: Introductionmentioning
confidence: 99%